Impacts of industrial developments on the distribution and movement ecology of wolves (Canis lupus) and woodland caribou (Rangifer tarandus caribou) in the South Peace region of British Columbia. - Williamson-Ehlers, Elizabeth Parr (Author); Johnson, Christopher (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
Habitat alterations from anthropogenic disturbances across northeastern British Columbia have resulted in large-scale modifications to predator-prey dynamics. I used GPS collar locations and field data to quantify the responses of wolves (Canis lupus) and woodland caribou (Rangifer tarandus caribou) to the cumulative effects of industrial disturbance. I developed seasonal resource selection functions for caribou and count models of habitat occupancy for wolves. I also related wolf movements to caribou habitat and industrial features. Caribou occupying the boreal forest likely are more at risk from industrial developments. My results suggest that caribou occupying these ecosystems are subject to disturbance by human activity and a greater risk of spatial interactions with wolves. However, these relationships are complicated by the positive and negative responses of wolves to landscape change and the distribution of other prey and predator species. --P. i. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1805687